Medical Students' Perceptions, Knowledge, and Competence in Treating Neurodivergent, Disability, and Chronic Illness (NDCI) Populations: Results from a Cross-Sectional Study - Emily Hotez; Maya Ayoub; Julianna Rava; Zina Jawadi; Kashia A. Rosenau; Lauren Taiclet; Leane Nasrallah; Charlotte Poplawski; Alice A. Kuo (University Library System, University of Pittsburgh, 2022)
Background: Globally, Neurodivergent, Disability, and Chronic Illness (NDCI) populations face significant health disparities. Lack of physician knowledge about NDCI is a key mechanism underlying these disparities. The current study aimed to describe medical students' perceptions, knowledge, and competence regarding NDCI. Methods: A cross-sectional study was carried out using an online survey of medical students at a large public university with no NDCI-specific curriculum (n = 97; response rate = 18%). The survey asked about students' perceptions, knowledge, and competence pertaining to NDCI populations. Results: Most (n = 93, 96%) indicated it is important for physicians to understand the influence of NDCI on patient health and clinical encounters. Yet only seven (7%) and 15 (15%) reported that the NDCI curriculum in their medical school was sufficient, and they felt comfortable taking care of patients with NDCI respectively. Most (n = 87, 90%) wanted their medical school to provide additional NDCI training. Few reported high knowledge about ableism (n = 12, 12%), self-determination (n = 7, 7%), coordinating care (n = 4, 4%) and accommodations (n = 10, 10%). Few indicated high competence in cognitive, physical, social-emotional, and other NDCI types (n = 7 - 32, 7-33%). Existing knowledge often came from personal experiences or the news and media. Conclusion: Findings demonstrated the gaps in medical education, as exemplified by medical students surveyed in one U.S. public university. Results can inform efforts to ameliorate global health disparities associated with a lack of physician knowledge about NDCI.